MENGUATKAN KEPUTUSAN PILIHAN MELALUI STRATEGI VIRAL MARKETING DAN WORD OF MOUTH (WOM) - Cahyanti, Mega Mirasaputri (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2022)
In approximately March 2020, Institute Asia become viral through social media, television media, and many more. Besides, the number of new students surprisingly increase compared to last year, even though in this year, many private campuses have a decreasing amount of new students. That’s why the researcher tries to figure out whether viral marketing, social media marketing, and WOM have an effect on the new student make a decision on choosing the campus. This research method is using multiple linear regression, with the number of sampling is 155 respondents. The sampling technique was used is simple random sampling by google form. The results in this research showed that viral marketing, WOM, have a positive and significant effect on new student make a decision on choosing the campus. Besides, social media marketing has no significant effect on a decision on choosing a campus.